2016
DOI: 10.1002/smll.201601234
|View full text |Cite
|
Sign up to set email alerts
|

Tunable Lipidoid‐Telodendrimer Hybrid Nanoparticles for Intracellular Protein Delivery in Brain Tumor Treatment

Abstract: A strategy to precisely engineer lipidoid‐telodendrimer binary hybrid nanoparticles that offer enhanced cell membrane permeability for therapeutic proteins to reach the intracellular targets is established. The highly controllable biochemical and physical properties of the nanoparticles make them promising for protein‐based brain cancer treatment with the assistance of convection‐enhanced delivery.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
13
0

Year Published

2017
2017
2020
2020

Publication Types

Select...
8
2

Relationship

4
6

Authors

Journals

citations
Cited by 17 publications
(13 citation statements)
references
References 51 publications
0
13
0
Order By: Relevance
“…[62, 63] DOX has a positively charged amine group, which should be able to migrate under electric field. Being stably loaded in a nanocarrier, DOX should be trapped in the loading well due to the size effects.…”
Section: Resultsmentioning
confidence: 99%
“…[62, 63] DOX has a positively charged amine group, which should be able to migrate under electric field. Being stably loaded in a nanocarrier, DOX should be trapped in the loading well due to the size effects.…”
Section: Resultsmentioning
confidence: 99%
“…The polycationic molecules or complexes were reported to be toxic for many cell lines. [2, 4, 34] HT-29 colon cancer cell line was selected as a model cell line to investigate the cytotoxicity of protein-polycation and protein-polycation-PEG 5k (OAOA-L-CHO) 4 nanocomplexes. The cell viability results after a 72-h continuous incubation at 37 °C in Fig.…”
Section: Resultsmentioning
confidence: 99%
“…In another interesting study, telodendrimers based on PEG-poly(lysine) containing cholic acid and/or cholesterol were investigated for the delivery of proteins across the blood–brain barrier. Using bovine serum albumin functionalized with fluorescent dye Cy5, it was found that telodendrimers assisted and improved the delivery of the protein into the brain [ 207 ]. The results are interesting, and suggest that the telodendrimer can overcome significant challenges in drug delivery across the blood–brain barrier.…”
Section: Telodendrimersmentioning
confidence: 99%